Growth of planktonic and biofilm culture of Nitrosomonas mobilis Ms1 in response to stoichiometric ammonia consumption. (October 2020) - Chawley, Parmita; Banerjee, Chiranjib; Jagadevan, Sheeja
Abstract: Nitrosomonas mobilis Ms1, a chemolithotrophic ammonia oxidizing bacterium, finds importance in wastewater treatment by virtue of its capability to oxidize ammonia into nitrite. However, its slow growth restricts its applicability in various bioremediation programmes. Response surface methodology with central composite design was employed to evaluate better growth yield (nitrification) of N. mobilis Ms1 with three culture medium variables, namely ammonia, sodium bicarbonate and pH. Enhanced nitrification was achieved with 6.36 mM NH3, 13.41 mM NaHCO3 and 8.8 pH. A general stoichiometric equation for redox reaction pertaining to biomass synthesis was formulated, and 0.012 g/L of biomass was estimated from the optimized medium. The optimized medium components were used to study the biofilm forming ability of N. mobilis Ms1. It was further characterized for its morphology and biochemical composition. Extra-polymeric substances (EPS) of the biofilm was found to be rich in protein. Qualitative analysis of fatty acid methyl ester (FAME) profile of suspended culture and biofilm reveals several saturated and unsaturated fatty acids. FAME consisting of C12:0 and C12:1 methyl esters can be regarded as the biomarkers of N.mobilis Ms1. Graphical abstract: Image 1 Highlights: Optimization of N. mobilis Ms1 culture medium by response surface methodology. Stoichiometric equation estimated synthesis of 0.11g of biomass/g NH3 –N. N. mobilis Ms1 produced 'feathered' like biofilm of 12 μM thickness. EPS in biofilm was found to be rich in protein. Presence of C12:0 and C12:1 methyl ester indicated FAME biomarkers.